2014
DOI: 10.1128/jvi.02333-14
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Nef and Vpu Are Functionally Redundant Broad-Spectrum Modulators of Cell Surface Receptors, Including Tetraspanins

Abstract: IMPORTANCEIn this paper, we define that HIV-1 Nef and Vpu display a surprising functional overlap and affect the cell surface exposure of a previously unexpected breadth of cellular receptors. Our analyses furthermore identify the tetraspanin protein family as a previously unrecognized target of Nef and Vpu activity. These findings have implications for the interpretation of effects detected for these accessory gene products on individual host cell receptors and illustrate the coevolution of Nef and Vpu functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
83
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 115 publications
(135 reference statements)
8
83
0
1
Order By: Relevance
“…1C and D), Nef also contributes to the phenomenon, specifically by downregulating the levels of tetraspanins at the plasma membrane. This finding parallels the results shown in a report by Haller and colleagues (45), which reveals a role in tetraspanin downregulation for Nef, as well as for Vpu.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…1C and D), Nef also contributes to the phenomenon, specifically by downregulating the levels of tetraspanins at the plasma membrane. This finding parallels the results shown in a report by Haller and colleagues (45), which reveals a role in tetraspanin downregulation for Nef, as well as for Vpu.…”
Section: Resultssupporting
confidence: 92%
“…Figure 1F shows that these mutants were still able to downregulate CD81, indicating that Vpu-mediated CD81 downregulation is independent of the 52/56 serine motif or the transmembrane domain of Vpu. This further confirms that this effect is not a by-product of either CD4 or BST-2/tetherin downregulation but, rather, constitutes a previously unrecognized function of Vpu, as was also revealed in the report by Haller and colleagues (45).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Although a direct interaction between HIV-1 Vpu and Nef is yet to be explored, Vpu and Nef share common activities to downregulate various host proteins (e.g., tetherin, CD4, and CD62L) (341,454,455). It has been shown that human tetherin (also termed BST2) interacts with Vpu (456)(457)(458)(459)(460)(461)(462)(463) and Nef (464).…”
Section: Vpu-tetherin/cd4-nef Associationmentioning
confidence: 99%
“…HIV-1 Nef also mediates the postendocytic targeting of internalized CD4 from the endosomes to the multivesicular body pathway, leading to the eventual degradation of CD4 in lysosomes (477). In addition to CD4, HIV-1 Vpu and Nef downregulate a broad spectrum of more than 32 cell surface receptors (454). Significant downregulation has been observed in the tetraspanin protein family harboring various cellular proteins (e.g., CD9, CD53, CD63, CD81, and CD82) that take part in membrane-based processes (454,478).…”
Section: Vpu-tetherin/cd4-nef Associationmentioning
confidence: 99%